The Shia Crescent - Szajkowski, Bogdan (The Copernicus Journal of Political Studies, 2018)
The study focuses on the recent rise in importance of the Shia branch of Islam. Ever since the success of the Iranian revolution, the Teheran regime has persistently claimed to be protector and promoter of the Shia interests outside its borders. Many Sunni rulers in the Middle East fear that the rising position of the Shia and Iran, in particular through its nuclear programme, will alter the traditional balance of power not only in the Gulf region but throughout the Arab world. The study introduces the term “the Shia crescent,” which has become a commonly used expression in popular, intellectual and political debates. As a geo-political term, it is used to describe a region of the Middle East where the majority population is Shia, or where there is a strong Shia minority in the population. The aim of this article is to examine critically the notion of the Shia crescent and suggest possible explanations on what is behind the rise of Shia power, how to account for it, and what are its consequences for the current system of international relations. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14763